ANALISIS BREAK EVEN POINT SEBAGAI PERENCANAAN LABA PADA USAHA KUE BANGKIT RIAU SYEMPANA DI KOTA PEKANBARU - Wenny Oktaviani; Rina Selva Johan; R.M.Riadi R.M.Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research was conducted at the business bangkit cake Riau Syempana. This study aims to analyze the level of BEP on bangkit Cake business Riau Syempana 2014 and to determine whether the profit plan that has been achieved with well defined. Analysis of the data used in this research is descriptive quantitative method. This research uses break-even analysis and margin of safety analysis, to determine the minimum number of sales and sales in a safe state before the company suffered losses. The results of this study indicate that the number of sales that must be conducted by a minimum of bangkit cake business Riau syempana so as not to incur a loss in 2014 amounting to Rp 119,345,707.66. In 2014 the margin of safety achieved by bangkit cake business riau syempana is 48.04%. To achieve a profit that has been set in the year 2014 in the amount of Rp 55.120.800, then the bangkit cake business Syempana must sell a minimum of Rp 247.236.194,9. Therefore, the analysis of the BEP should be applied in planning corporate profits. Making it easier to analyze the factors that affect the achievement of corporate profits in the future.Key words : Break Even Point, profit planning.